The formation and aqueous alteration of CM2 chondrites and their relationship to CO3 chondrites: A fresh isotopic (O, Cd, Cr, Si, Te, Ti, and Zn) perspective from the Winchcombe CM2 fall - Greenwood, Richard C.; Findlay, Ross; Martins, Rayssa; Johnson, Diane (Wiley, 2023)
As part of an integrated consortium study, we have undertaken O, Cd, Cr, Si, Te, Ti, and Zn whole rock isotopic measurements of the Winchcombe CM2 meteorite. δ66Zn values determined for two Winchcombe aliquots are +0.29 ± 0.05‰ (2SD) and +0.45 ± 0.05‰ (2SD). The difference between these analyses likely reflects sample heterogeneity. Zn isotope compositions for Winchcombe show excellent agreement with published CM2 data. δ114Cd for a single Winchcombe aliquot is +0.29 ± 0.04‰ (2SD), which is close to a previous result for Murchison. δ130Te values for three aliquots gave indistinguishable results, with a mean value of +0.62 ± 0.01‰ (2SD) and are essentially identical to published values for CM2s. ε53Cr and ε54Cr for Winchcombe are 0.319 ± 0.029 (2SE) and 0.775 ± 0.067 (2SE), respectively. Based on its Cr isotopic composition, Winchcombe plots close to other CM2 chondrites. ε50Ti and ε46Ti values for Winchcombe are 3.21 ± 0.09 (2SE) and 0.46 ± 0.08 (2SE), respectively, and are in line with recently published data for CM2s. The δ30Si composition of Winchcombe is −0.50 ± 0.06‰ (2SD, n = 11) and is essentially indistinguishable from measurements obtained on other CM2 chondrites. In conformity with petrographic observations, oxygen isotope analyses of both bulk and micromilled fractions from Winchcombe clearly demonstrate that its parent body experienced extensive aqueous alteration. The style of alteration exhibited by Winchcombe is consistent with relatively closed system processes. Analysis of different fractions within Winchcombe broadly support the view that, while different lithologies within an individual CM2 meteorite can be highly variable, each meteorite is characterized by a predominant alteration type. Mixing of different lithologies within a regolith environment to form cataclastic matrix is supported by oxygen isotope analysis of micromilled fractions from Winchcombe. Previously unpublished bulk oxygen isotope data for 12 CM2 chondrites, when combined with published data, define a well-constrained regression line with a slope of 0.77. Winchcombe analyses define a more limited linear trend at the isotopically heavy, more aqueously altered, end of the slope 0.77 CM2 array. The CM2 slope 0.77 array intersects the oxygen isotope field of CO3 falls, indicating that the unaltered precursor material to the CMs was essentially identical in oxygen isotope composition to the CO3 falls. Our data are consistent with earlier suggestions that the main differences between the CO3s and CM2s reflect differing amounts of water ice that co-accreted into their respective parent bodies, being high in the case of CM2s and low in the case of CO3s. The small difference in Si isotope compositions between the CM and CO meteorites can be explained by different proportions of matrix versus refractory silicates. CMs and COs may also be indistinguishable with respect to Ti and Cr isotopes; however, further analysis is required to test this possibility. The close relationship between CO3 and CM2 chondrites revealed by our data supports the emerging view that the snow line within protoplanetary disks marks an important zone of planetesimal accretion.
Special Issue: The science of the Winchcombe meteorite